EVIDENCE OF ALPINE EPIGENETIC IRON-MANGANESE ORE DEPOSITION IN SOUTHERN AND CENTRAL KAZAKHSTAN - Levin V.N. (My University, 1989)
Systematic drilling recently done during prospecting surveys in various parts of the Chu-Sarysu and the Ili depressions disclosed iron-manganese mineralization in Upper Cretaceous and Paleogene continental deposits. Their geologic and mineralogic study revealed the epigenetic origin of such mineralization and its morphologically unusual mode of localization in the unconsolidated, gently dipping deposits of these depressions. Our study of four separate localities here resulted in the detection of steeply dipping, pipe-shaped ore bodies and proved that they are genetically related to stratiform ore bodies. The iron-manganese mineralization found in unlithified, continental cratonic deposits of Late Cretaceous-Paleogene age should be regarded as products of the Alpine epoch of iron-manganese ore deposition, manifested in connection with post-Paleogene tectonic activity.
Keywords: Cretaceous; Paleogene; Кайнозой::Палеоген; Cenozoic::Paleogene; Mesozoic::Cretaceous; Мезозой::Меловая